The Ghrelin/Growth Hormone Secretagogue Receptor System Is Involved in the Rapid and Sustained Antidepressant-Like Effect of Paeoniflorin - Zhang, Yuan; Zhu, Min-Zhen; Qin, Xi-He; Zeng, Yuan-Ning; Zhu, Xin-Hong (Frontiers in Neuroscience, 2021)
Major depressive disorder (MDD) is a debilitating mental illness globally. Although significant progress has been made in the development of therapeutic agents, fewer than half of all patients respond to currently available antidepressants. Therefore, the need to develop new classes of antidepressants is urgent. Here, we found that paeoniflorin (PF) produced rapid and sustained antidepressant-like effects in multiple animal models of depression, including the forced swimming test, the novelty-feeding test, and the chronic mild stress (CMS). Moreover, PF treatment decreased the plasma levels of ghrelin, whereas the plasma level of acyl-ghrelin and the ratio of acyl-ghrelin/total ghrelin were unaffected. Furthermore, PF significantly increased the expression of the growth hormone secretagogue receptor 1α (GHSR, encoded by GHSR) in the intestine. Meanwhile, the brain levels of GHSR were marginally downregulated following subchronic treatment with PF. The genetic deletion of Ghsr attenuated the antidepressant-like effects of PF during CMS. These results suggest that increased intestinal GHSR expression mediates the antidepressant-like effect of PF. Therefore, understanding peripheral ghrelin/GHSR signaling may provide new insights for screening rapid-acting and sustained antidepressants.